The Challenge of Exemplification in Crisis Communication - Deborah D. Sellnow; Timothy L. Sellnow (Journal of Applied Communications, 2014)
This case study characterizes the crisis communication challenges and potential response strategies of organizations facing crises of perception created by media exemplars. Exemplars are created through repeated news stories made memorable by highly vivid language, shocking visual materials, and evocative personal testimonies. ABC’s portrayal of Lean Finely Textured Beef as “pink slime” is provided as a case for analysis. The study concludes that organizations responding to crises of perception are at an extreme disadvantage when their standard operating procedures are portrayed negatively as exemplars. In addition, stigmatization increases an organization’s susceptibility to exemplars. Finally, appeals to neutral parties have the potential to bring some degree of added credibility to organizations responding to crises of perceptions caused by exemplars.
Keywords: Food safety; risk communication; crisis communication; news framing